Classification of Nek Ali Coffee’s customers using the fishers method - Khairul Umam; Suhartati Suhartati; M Hasbi; Dwi Fadhiliani; Annisa Dewi (Geuthèë Institute, Aceh, 2023)
This study uses discriminant analysis which aims to determine a model or formula that determines consumer groups who are interested in powdered, coffee bean, or instant coffee variants from several influencing variables, including coffee caffeine content, sugar content contained in coffee, coffee roasting level, quality coffee, coffee price, consumer age, consumer health, time of day consumer activity, and durability. The subjects of this research were the consumers of Nek Ali's Coffee with a total of 82 samples. The data obtained in this study were analyzed using discriminant analysis of three groups, namely the consumer group who are interested in coffee powder, coffee beans, and instant coffee. This study uses Discriminant Fisher's through SPSS software, the discriminant model or formula is obtained, as follows:Y1 = (0.08)X1 + (0.948)X2 + (0.332)X3 + (0.633)X4 + (0.576)X5 – (0.003)X6 + (1.825)X7 – (1.140)X8 = 0Y2 = (0.012)X1 + (0.868)X2 + (0.351)X3 + (0.591)X4 + (0.621)X5 – (0.002)X6 + (1.841)X7 – (0.592)X8 = 0Y3 = (0.081)X1 + (0.944)X2 + (0.349)X3 + (0.607)X4 + (0.581)X5 – (0.002)X6 + (1.971)X7 – (0.592)X8 = 0